How financial performance, firm characteristics, and board composition shape sustainability report disclosure? - Zaisabilla, Clarissa Dyah; Widoretno, Astrini Aning (Jurnal Akademi Akuntansi, 2026)
Purpose: This study examines the effects of Profitability, Firm Size, Firm Activity, the Audit Committee, and the Board of Directors on Sustainability Report Disclosure in energy sector companies in Indonesia. In particular, the study investigates how the presence of women on the audit committee and the board of directors influences the extent of sustainability report disclosure. Methodology/approach: This research analyzes a total of 156 observations selected purposively sampling, based on secondary data obtained from company financial reports and sustainability reports available on corporate websites and Indonesia Stock Exchange (IDX). Findings: The analysis shows that profitability, firm size, and firm activity have a significant and positive association with sustainability report disclosure. Furthermore, the presence of women on the audit committee does not significantly affect sustainability report disclosure, whereas the presence of women on the board of directors negatively influences the level of disclosure. Practical and Theoretical Contribution/Originality: The findings contribute to the development of stakeholder theory and resource dependence theory within the Indonesian setting. Research Limitation: This research is limited to energy sector firms in Indonesia. Future studies are encouraged to expand the scope by including other industries, additional countries, or other variables.